Estimation of Overhead Transmission Line Fault Distance Using Unsynchronized Two-Terminal Method - Syahputra, Ramadoni; Soesanti, Indah (Journal of Electrical Technology UMY, 2018)
This paper presents the estimation of transmission line fault distance using unsynchronized two-terminal method. In operation, high or extra-high overhead voltage transmission lines can be interrupted. The disturbance can come from internal or external interference, which is permanent or temporary. For permanent interference, the network operator must visit the location of the disturbance in order to fix it. Because the transmission line is very long, while it takes quick time to find out the location of the disturbance so that it can be repaired immediately, then a method is needed to find out the location of the disturbance. This research proposes a method for determining the location of faults based on voltage and current data at the time of interference from both ends of the transmission line. The interference voltage and current data need not be synchronized. The use of this data makes this method very simple and easy to use. However, the accuracy of the estimation results can still be relied upon. In this study, a simulation was carried out on a two-end transmission line. The transmission line has a phase disturbance to the ground. The noise resistance applied in the simulation is 0 ohms, 10 ohms, 50 ohms, and 100 ohms. The results showed that the highest estimated error was 0.3%, which indicates that this method has a high degree of accuracy.